2015
DOI: 10.1104/pp.15.00461
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Branched-Chain Ketoacid Dehydrogenase Complex on Amino Acid Homeostasis in Arabidopsis

Abstract: The branched-chain amino acids (BCAAs) Leu, Ile, and Val are among nine essential amino acids that must be obtained from the diet of humans and other animals, and can be nutritionally limiting in plant foods. Despite genetic evidence of its importance in regulating seed amino acid levels, the full BCAA catabolic network is not completely understood in plants, and limited information is available regarding its regulation. In this study, transcript coexpression analyses revealed positive correlations among BCAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
101
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 75 publications
(155 reference statements)
3
101
0
Order By: Relevance
“…In plants, BCAAs and their derivatives contribute to growth, defense, and the production of food flavor components (Kang et al, 2006;Yoshikawa et al, 1995;Zeier, 2013;Kimball and Jefferson, 2006;Gonda et al, 2010;Galili et al, 2016). In addition, BCAA catabolism provides an alternative source of energy in plants under long-term dark treatment conditions (Peng et al, 2015;Kochevenko et al, 2012). Moreover, acetohydroxyacid synthase (AHAS), the committed enzyme of Val biosynthesis, is the target of four classes of commercial herbicides, and numerous plant herbicide resistance AHAS alleles have been reported (Jander et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants, BCAAs and their derivatives contribute to growth, defense, and the production of food flavor components (Kang et al, 2006;Yoshikawa et al, 1995;Zeier, 2013;Kimball and Jefferson, 2006;Gonda et al, 2010;Galili et al, 2016). In addition, BCAA catabolism provides an alternative source of energy in plants under long-term dark treatment conditions (Peng et al, 2015;Kochevenko et al, 2012). Moreover, acetohydroxyacid synthase (AHAS), the committed enzyme of Val biosynthesis, is the target of four classes of commercial herbicides, and numerous plant herbicide resistance AHAS alleles have been reported (Jander et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthesis and catabolism both play roles in BCAA regulation in plants (Galili et al, 2016). Arabidopsis mutants blocked in BCAA degradation accumulate BCAAs in seeds of plants grown under standard environmental conditions (Angelovici et al, 2013;Gu et al, 2010;Lu et al, 2011) and in leaves of dark-treated plants (Peng et al, 2015;Araújo et al, 2010), implicating BCAA catabolism in seed BCAA homeostasis and as an alternative energy source under energy-deprived conditions. These catabolic enzymes are coregulated at steady state mRNA level under diel and extended darkness conditions as well as during seed development, consistent with the mutant results (Peng et al, 2015;Uygun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At high concentrations, this inhibition can lead to starvation of a downstream metabolic product, Met, which inhibits plant growth (Bright et al, 1982;Rognes et al, 1983;Heremans and Jacobs, 1995). In addition, several amino acid catabolic products, such as those emanating from branched-chain amino acids (BCAAs) or Lys degradation pathways, can be channeled toward cellular energy production under both standard and stress growth conditions (Angelovici et al, 2009(Angelovici et al, , 2011 Araújo et al, 2010;Peng et al, 2015).Reconstructions of seed metabolic networks in several model species and tissues have offered important insights into these underlying metabolic interactions and regulation Toubiana et al, 2013Toubiana et al, , 2015. For example, a correlation-based network metabolic [ reconstruction of FAA levels revealed that individual FAAs are strongly correlated during seed development compared with leaf or fruit development (Toubiana et al, 2012), which suggests a much tighter interaction of this metabolic network in seeds.…”
mentioning
confidence: 99%
“…At high concentrations, this inhibition can lead to starvation of a downstream metabolic product, Met, which inhibits plant growth (Bright et al, 1982;Rognes et al, 1983;Heremans and Jacobs, 1995). In addition, several amino acid catabolic products, such as those emanating from branched-chain amino acids (BCAAs) or Lys degradation pathways, can be channeled toward cellular energy production under both standard and stress growth conditions (Angelovici et al, 2009(Angelovici et al, , 2011Araújo et al, 2010;Peng et al, 2015).…”
mentioning
confidence: 99%